SNAIL’S SLIME AS AN ALTERNATIVE HYDROGEL FOR HEALING BURNS WOUND ON RATS (Rattus norvegicus) SPRAGUE DAWLEY STRAIN - - Muhartono; Hendra Tarigan Sibero; Bayu Putra Danan Jaya (JUKE Unila, 2014)
Background: Burns is a serious health problem that can lead to morbidity, disability, and mortality. One of the standard treatment of the burns that are known at this time is hydrogel. Despite treatment with hydrogel gives good results, it is quite expensive, so it is necessary to choose the cheaper, easier, and does not cause side effects treatment such as snail slime or mucus. This study aims to determine whether the snail mucus can act as a substitute for the hydrogel in the treatment of burns at Sprague Dawley rat strain. Method: This study is a comparative experimental study in the laboratory of Anatomical Pathology, Faculty of Medicine, Universitas Lampung, during August-November 2013. This study uses 15 white rats that were given burns, then divided into 3 treatment groups which were control group, the group given hydrogel, and the group given snail’s mucus for 14 days. Statistical analysis was performed using One Way Anova test and Post Test Hoct LSD. Result: The test results of the histopathological healing of burns showed significant differences between the hydrogel group and controls (p=0.017), while the snail mucus has no significant difference with the control group (p=0.373). Conclusion: Snail mucus can not be used as an alternative hydrogels for healing burns on white rats (Rattus norvegicus) Sprague Dawley strain. [JuKe Unila 2014; 4(8):144-150)